Universities as orchestrators of the development of regional innovation ecosystems in emerging economies - Thomas, Elisa; Faccin, Kadigia; Asheim, Bjørn Terje (Growth and change, 2021)
This paper analyses the role of universities as orchestrators of the development of a regional ecosystem that is conducive to innovation and entrepreneurship. We argue that universities in emerging economies, due to many social challenges, must go beyond their missions of teaching, research, and collaboration with industry for innovation. We present a unique case study of an alliance of three universities in Porto Alegre, Brazil that, in addition to being competitors in the above‐mentioned missions, are orchestrating a network of stakeholders in this region to develop an ecosystem for innovation and entrepreneurship. We demonstrate that universities perform several orchestration processes that are consistent with the literature, such as fostering knowledge mobility, managing innovation appropriability, and increasing network stability. Furthermore, we found differences in how innovation ecosystems are orchestrated as compared to firm networks. In the case of innovation ecosystems, appropriability reaches the broader region, and the benefits are not limited to participant stakeholders. Such orchestration processes emerge when universities take on leadership positions in the region; they can influence the beginning of collective actions and projects as well as transfer responsibility, delegating power to other actors in the network.